Mid-term outcomes with adult endovascular treatment of coarctation of the aorta. (15th January 2021) - Nagendran, Jeevan; Mathew, Anoop; Kang, Jimmy J.H.; Bozso, Sabin J.; Hong, Yongzhe; Taylor, Dylan A.
Abstract: Background: This study examines the contemporary medium- and long-term outcomes of endovascular repair of aortic coarctation in the adult. Methods: We reviewed the clinical and imaging data of 56 consecutive adult patients with aortic coarctation who underwent endovascular repair at the Mazankowski Alberta Heart Institute, Edmonton, Alberta, Canada, from 2003 to 2018. Results: There were 20 (35.7%) female and 36 (64.3%) male patients (including 9 re-intervention cases) with a mean age of 33.6 ± 13.6 years. Thirty-seven (66.1%) were treated with balloon-expandable covered stent and 12 (21.4%) were treated with balloon-expandable bare-metal stent. Pressure gradients decreased from baseline level of 27.99 ± 12.75 (8–70) mm Hg to 5.33 ± 4.42 (0–17.5) mm Hg following the procedure. There were 2 (3.6%) procedure related complications (aortic dissection [ n = 1] and stent malposition [n = 1]). During a median (Q1 - Q3) follow up of 5.36 (2.28–7.58) years, 2 deaths (4.2%) and 9 (19%) re-interventions occurred, and the overall survival was 95.8%. Conclusion: Percutaneous coarctoplasty, with either covered or bare metal stents, is a safe and durable option for aortic coarctation repair with excellent long-term survival. Highlights: Adult congenital endovascular treatment of aortic coarctation yields excellent long-term survival Adult congenital endovascular coarctation repair has a low complication rate at a median follow up time of 5.36 years Adult congenital endovascular treatment of aortic coarctation demonstrates safety and durability of the endovascular repair